Preliminary Study of Coping, Perceived Control, and Depressive Symptoms in Youth with Sickle Cell Anemia. Issue 6 (August 2021) - Prussien, Kemar V.; Siciliano, Rachel E.; Ciriegio, Abagail E.; Lee, Chelsea A.; DeBaun, Michael R.; Jordan, Lori C.; Compas, Bruce E.
ABSTRACT: Objective: The primary objective of this study was to test perceived controllability of stressors as a moderator of the association between coping and depressive symptoms in children and adolescents with sickle cell anemia (SCA). Method: Twenty-eight children and adolescents (Mage = 11.71, SD = 4.31; 60.7% female) with SCA were enrolled. Caregivers provided reports of child and adolescent coping using the Response to Stress Questionnaire (RSQ), perceived control of stressors using the RSQ, and depressive symptoms using the Child Behavior Checklist. Children and adolescents also completed Wechsler assessments of working memory and verbal comprehension. Results: Secondary control coping (i.e., cognitive reappraisal, positive thinking, acceptance, and distraction) was a significant predictor of depressive symptoms such that greater use of secondary control coping was related to fewer reported depressive symptoms when accounting for perceived control of stress and neurocognitive variables. Furthermore, perceived control of peer-related stress was a significant moderator of the association between secondary control coping and depressive symptoms such that there was a significant negative association of secondary control coping with depressive symptoms only for low perceived control. Conclusion: Secondary control coping may be particularly helpful for reducing depressive symptoms when adolescents' peer-related stressors are perceived as uncontrollable. Interventions to reduce internalizing problems in this population should consider teaching children and adolescents secondary control coping skills in addition to skills in identifying uncontrollable sources of stress. Abstract : This article has supplementary material on the web site: www.jdbp.org.